2013
DOI: 10.3390/ijms14047061
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity Revealed by Single Nucleotide Polymorphism Markers in a Worldwide Germplasm Collection of Durum Wheat

Abstract: Evaluation of genetic diversity and genetic structure in crops has important implications for plant breeding programs and the conservation of genetic resources. Newly developed single nucleotide polymorphism (SNP) markers are effective in detecting genetic diversity. In the present study, a worldwide durum wheat collection consisting of 150 accessions was used. Genetic diversity and genetic structure were investigated using 946 polymorphic SNP markers covering the whole genome of tetraploid wheat. Genetic stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 69 publications
9
87
3
2
Order By: Relevance
“…Similarly, cotton and other plants high-resolution genetic linkage map and gene tagging have used SNP in their evaluation (Cho et al 2011;Mammadov et al 2012;Li et al 2014). Massive availabilities of SNP markers open the possibility of tagging genes controlling important agronomic characters and supporting breeding programs (Ren et al 2013). The frequency of SNP occurrences in the plant genome is as many as one SNP for every 31 base pair (bp) up to every 124 bp of plant genome (Eulgem et al 2000;Ching et al 2002;Zhang and Wang 2005;Fang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cotton and other plants high-resolution genetic linkage map and gene tagging have used SNP in their evaluation (Cho et al 2011;Mammadov et al 2012;Li et al 2014). Massive availabilities of SNP markers open the possibility of tagging genes controlling important agronomic characters and supporting breeding programs (Ren et al 2013). The frequency of SNP occurrences in the plant genome is as many as one SNP for every 31 base pair (bp) up to every 124 bp of plant genome (Eulgem et al 2000;Ching et al 2002;Zhang and Wang 2005;Fang et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…(4) SSRs are more easily scorable than most morphological features, (5) SSR detection is highly reproducible and can reveal intraspecific homology. (6) The abundance of SSRs enhances the likelihood of linkage to specific agronomic traits; for instance, SSR results revealed large genetic distances between certain landraces of rice, thus evaluation of genetic diversity and genetic structure in crops has important implications for plant breeding programs and the conservation of genetic resources (Ren et al, 2013). The result of cluster analysis revealed that there was to significant correlation between the aromatic feature and genetic similarity.…”
Section: Discussionmentioning
confidence: 82%
“…Newly developed single nucleotide polymorphism (SNP) markers are effective in detecting genetic diversity (Ren et al, 2013). SSR and single nucleotide polymorphic (SNP), the two most robust markers for identifying rice varieties were compared for assessment of genetic diversity and population structure (Singh et al, 2013).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…Newly developed single nucleotide polymorphism (SNP) markers are effective in detecting genetic diversity (Ren et al 2013), but in some cases larger number of markers need to be used due to large genome of wheat. If no pedigree information is available the breeder may use the molecular marker data for selecting the parents/lines for crossing.…”
Section: Discussionmentioning
confidence: 99%
“…To date, a variety of molecular techniques have been in usage in wheat such as restriction fragment length polymorphisms (RFLP), random polymorphic amplified DNA (RAPD) and amplified frag-ment length polymorphisms (AFLP), which have been used successfully for genetic mapping, phylogenetic relationships, comparative genomic studies, and genetic diversity evaluation. However, none of them have been used extensively in breeding programs because they do not meet the requirements for efficient application in marker assisted selection (MAS) (Ren et al 2013).…”
Section: Introductionmentioning
confidence: 99%